Role of Education Management to Expediate Supply Chain Management: A case of Indonesian Higher Educational Institutions - Dahlena Sari Marbun; Sulaiman Effendi; Henny Zurika Lubis; Ikbar Pratama (International Journal of Supply Chain Management, 2020)
Objective of this study is to examine the role of universities in supply chain management (SCM) in Indonesia. Among the Indonesian universities, the supply chain education is included, however, academic scholars did not pay the intention to examine the effect on SCM. Therefore, this study considered to examine the relationship between higher education institutions and SCM. Various key university related factors were considered, namely; university education system, supply chain education at university level and the role of university management. Data were collected from university teachers in Indonesia. Four hundred (400) survey questionnaires were used to collect the data. Collected data were analysed through structural equation modeling (SEM) technique. In response to the objective of the study, it is revealed that universities have significant role in SCM. Supportive education system of universities shows positive effect in SCM with mediating role of supply chain education. Additionally, university management as moderating variable strengthen the relationship between supply chain education and SCM.